Screening of lysyl oxidase (LOX) and lysyl oxidase like (LOXL) enzyme expression and activity in preterm prelabor rupture of fetal membranes - Polettini, Jossimara [UNESP]; Silva, Marcia G. [UNESP]; Kacerovsky, Marian; Syed, Tariq A.; Saade, George R.; Menon, Ramkumar (Walter De Gruyter Gmbh, 2016)
Objective: Lysyl oxidase (LOX) and LOX like enzymes (LOXL1-4) physiologically remodel extracellular matrix and pathologically contribute to cellular senescence under oxidative stress (OS). We characterized LOX and LOXL expressions and activity in human fetal membranes. Methods: Human fetal membranes from women with uncomplicated pregnancies at term, preterm birth with intact membranes (PTB) or preterm prelabor rupture of membranes (pPROM), and in vitro fetal membranes stimulated with water-soluble cigarette smoke extract (CSE), an OS inducer, were analyzed by real-time PCR and immunohistochemistry for LOX and LOXL (1-4) expression and localization. LOX activity was measured by fluorometric assay. Results: LOX gene expression was similar to 2.5-fold higher in fetal membranes from pPROM compared to PTB and term (P = 0.02). LOX and LOXL1, 2 and 4 were localized to both amniotic and chorionic cells, whereas LOXL3 was limited to chorion. LOX and LOXL isoform expressions were not different between CSE treated and untreated groups, while LOX activity was increased in the presence of an antioxidant (P = 0.02). Conclusions: Increase of LOX expression in pPROM, an OS-related disease, and the apparent inhibition of LOX activity by CSE restored by antioxidant treatment suggest that reactive oxygen species might influence LOX-mediated tissue remodeling in fetal membranes. Balanced antioxidant supplementation during pregnancy may reduce the risk of pPROM by increasing LOX activity.
Keywords: Antioxidant; cigarette smoke; oxidative stress; preterm birth